MEASURING INDONESIAN EFL TEACHERS’ TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE IN THE POST-PANDEMIC ERA: DO DEMOGRAPHICAL ISSUES MATTER? - Ahmad Syafi'i; Syafiul Anam (Premise: Journal of English Education and Applied Linguistics, 2022)
This research aimed to measure Indonesian EFL teachers' Technological Pedagogical Content Knowledge (TPACK) in the post-pandemic era. EFL teachers must have balanced technological knowledge, pedagogical knowledge, content knowledge, technological pedagogical knowledge, pedagogical content knowledge, technological pedagogical content knowledge, and web content knowledge since the Covid-19 pandemic has altered mainstream educational practices. Face-to-face instruction has shifted to online instruction, affecting EFL teachers' TPACK. The researcher hypothesized a significant difference in gender, age, and length of teaching experience in Indonesian EFL teachers' TPACK, particularly during online learning. The participants of this study were 24 Indonesian EFL teachers from 22 different schools and affiliations. An adopted TPACK questionnaire was administered to measure the Indonesian EFL teachers' TPACK during online learning. It consists of 25 total items. The data were calculated using SPSS version 26 software to determine each datum's U-value, mean, and standard deviation. This research revealed no significant difference in all aspects of TPACK based on the EFL teachers' gender. Moreover, there was no significant difference in the five aspects of TPACK based on the five age categories, except in Content Knowledge (CK). Furthermore, there was also no statistical difference in all aspects of TPACK based on the EFL teachers' length of teaching experience. However, age and teaching experience, particularly, contribute to shaping the Indonesian EFL teachers' level of TPACK.